Wurttemberkové v Olešnici = The Württemberg dynasty in Olesznica - Županič, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The last member of the Poděbrady dynasty in Silesia was the Duke Charles II. Frederick (1593-1647). His daughter from his first marriage with Duchesse Anna Sophia von Sachsen-Altenburg (1598-1641). Elisabeth-Maria (1625-1686) became heiress of the country. Charles II. Frederick married Elisabeth-Maria with the Duke Silvius Nimrod of Württemberg (1622-1664), and in his will appointed him the heir of the Duchy of Oels (Olesznica). The children of Elisabeth-Mary and Silvius Nimrod were titled Dukes of Württemberg-Oels and possessed the Duchy of Oels as well as Moravian houses and lands of the Poděbrady dynasty.
Keywords: Württemberg; dynastia wirtemberska; Olesznica (Czechy)